Collagen type IV‐related nephropathies in Portugal: pathogenic COL4A3 and COL4A4 mutations and clinical characterization of 25 families. (10th November 2014) - Nabais Sá, M.J.; Storey, H.; Flinter, F.; Nagel, M.; Sampaio, S.; Castro, R.; Araújo, J.A.; Gaspar, M.A.; Soares, C.; Oliveira, A.; Henriques, A.C.; da Costa, A.G.; et al.
<x xml:space="preserve">Abstract</x> Pathogenic mutations in genes COL4A3/COL4A4 are responsible for autosomal Alport syndrome (AS) and thin basement membrane nephropathy (TBMN). We used Sanger sequencing to analyze all exons and splice site regions of COL4A3/COL4A4, in 40 unrelated Portuguese probands with clinical suspicion of AS/TBMN. To assess genotype–phenotype correlations, we compared clinically relevant phenotypes/outcomes between homozygous/compound heterozygous and apparently heterozygous patients. Seventeen novel and four reportedly pathogenic COL4A3/COL4A4 mutations were identified in 62.5% (25/40) of the probands. Regardless of the mutated gene, all patients with ARAS manifested chronic renal failure (CRF) and hearing loss, whereas a minority of the apparently heterozygous patients had CRF or extrarenal symptoms. CRF was diagnosed at a significantly younger age in patients with ARAS. In our families, the occurrence of COL4A3/COL4A4 mutations was higher, while the prevalence of XLAS was lower than expected. Overall, a pathogenic COL4A3/COL4A4/COL4A5 mutation was identified in >50% of patients with fewer than three of the standard diagnostic criteria of AS. With such a population background, simultaneous next‐generation sequencing of all three genes may be recommended as the most expedite approach to diagnose collagen IV‐related glomerular basement membrane nephropathies.